Differences between 3D printed concrete and 3D printing reinforced concrete technologies: a review - Momeni, Komeil; Vatin, Nikolai Ivanovich; Hematibahar, Mohammad; Gebre, Tesfaldet Hadgembes (Frontiers in Built Environment, 2025)
This review aims to provide a comprehensive analysis of the difference between 3D printed concrete (3DPC) and 3D printing reinforced concrete (3DPRC) technologies, as well as potential future paths for these technologies based on current consolidated approaches. Although 3D printed reinforced concrete technology attempts to strengthen reinforced concrete using 3D printing technologies with polymer ingredients, 3D printed concrete technology concentrates on printing concrete for building concrete structures. In recent years, both technologies have advanced rapidly and become a global research innovation hotspot due to their advantages over traditional construction technology, such as high building efficiency, low labor costs, and less construction waste. Unfortunately, there are several issues with 3DPC and 3DPRC technologies, including competing rheological requirements, integrating hurdles, inadequate interlayer bonding, and anisotropic properties of the material that result in lacking structural performance. The findings of the investigation discuss research gaps and theoretical possibilities for future development in both 3D printing technologies, which can advance concrete technology and safeguard structures under various loads. In the present study, two distinct 3D printing technologies are analyzed, along with their respective uses in material and structural engineering. Additionally, the advantages, methods, and materials utilized for the two types of 3D printing technology are described, and the difficulties and solutions associated with using 3D printed concrete in real-world projects are demonstrated. None of the earlier investigations examined the differences between these two technologies. Although 3DPRC technologies aim to strengthen concrete by incorporating various forms of 3D printed technology, 3DPC technology has been studied for its mechanical qualities and concrete rheology. Meanwhile, engineers in 3D printed concrete technologies try to improve large-scale 3D printers and the mechanical properties of printed concrete, while 3D printing reinforced concrete engineers try to design new patterns of 3D reinforcing patterns due to the improved mechanical properties of concrete. The present study examines the differences between 3DPC and 3DPRC technologies.